ผลของกากไคทินจากฤดูปลูกแรกต่อผลผลิตของผักกาดหอม Lactuca sativa L. ในฤดูปลูกที่สอง - ภัทรพล พลูพัฒน์ธนกิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
Chitin–rich residue (CRR), a natural polysaccharide derived from deacetylation process of chitosan production from chitin. Effects of CRR on growth and productivity of lettuce (Lactuca sativa L.) were investigated during two crop seasons. Growth, yield and some physiological characteristics including chlorophyll content, carotenoid content, SPAD, total phenolic compounds, ascorbic acid and antioxidant activity of CRR treated lettuce were determined in comparison with control plant with only cow manure addition. During the second crop, a remained CRR from the first crop was determined. Plant supplemented with CRR resulted in significant increases of chlorophyll content, carotenoid content, SPAD, phenolic compounds, ascorbic acid and antioxidant activity during the second crop and yield productivity in term of fresh weight, dry weight, leaf number and stem diameter during both crop seasons. Therefore, CRR treatment can stimulate lettuce growth for at least 2 crop seasons.